Speaking the unspeakable : religion, misogyny, and the uncanny mother in Freud's cultural texts - Jonte-Pace, Diane E. (Diane Elizabeth), 1951- (University of California Press, 2001)
In this bold rereading of Freud's cultural texts, Diane Jonte-Pace uncovers an undeveloped 'counterthesis, ' one that repeatedly interrupts or subverts his well-known Oedipal masterplot.
Keywords: Freud, Sigmund, -- 1856-1939.; Freud, Sigmund, -- 1856-1939; Freud, Sigmund.; Psychoanalysis and religion.; Feminist psychology.; Psychoanalysis.; Religion.; Feminism.; Psychoanalytic Theory; Religion; Feminism; Psychanalyse -- Aspect religieux.; Psychologie féministe.; Psychanalyse.; Féminisme.; psychoanalysis.; religion (discipline); feminism.; 77.14 psychoanalysis.; 11.06 psychology of religion.; PSYCHOLOGY -- Movements -- Psychoanalysis.; RELIGION -- Judaism -- General.; Psychoanalysis; Feminist psychology; Psychoanalysis and religion; Psychoanalyse; Feminismus; Godsdienst.; Vrouwenhaat.; Moedercomplex.